When does fakery in nature documentaries go too far and what about the scientists in them? - Goldman, Helle V. (Polar research, 2025)
This editorial reflects on deception in nature documentaries, ranging from trifling and, arguably, justifiable tricks to the outright hoaxes that gravely mislead viewers and damage public trust in science. Examples are drawn from Disney, BBC, Discovery Channel, Animal Planet and other productions. Scientists who are asked to appear in nature documentaries are advised to proceed with caution and to safeguard their right to speak publicly about falsehoods and dupery in such productions. The availability of inexpensive video-fabricating applications raises the spectre of additional problems.